Chèref-Nâmeh ou fastes de la nation kourde - Şeref Han, 1543-1603/04. (Westmead, Farnborough, Hants, England)
2 cilt 4 ciltte (1. c., 1. kitap 852 s. ; 1. c., 2. kitap 502 ; 2. c., 1. kitap 705 s. ; 2. c., 1. kitap 712 s.)